The effect of Cirsium arvense extract on antioxidant status in quail - Orhan, C.; Şahin, Nurhan.; Akdemir, F.; Markiewicz-Zukowska, R.; Borawska, M. H.; Isidorov, V. A.; Şahin, Kazım (Taylor & Francis Ltd, 2013)
1. The herb Creeping Thistle, Cirsium arvense (C. arvense), has been used in folk medicine due to its antioxidant and anti-inflammatory effects.2. The aim of this study was to investigate the effects of dietary C. arvense extract supplementation on performance, egg quality, nutrient digestibility and antioxidant status in quail.3. Quails (n=150) were allocated randomly to one of the three dietary treatments: basal diet and basal diet enriched with 100 and 200mgC. arvense extract per kg diet.4. Dietary enrichment with C. arvense extract altered neither performance and egg quality parameters nor nutrient digestibility. Although there were no changes in concentrations of vitamin A and E in serum, liver and egg yolk, supplemental C. arvense extract decreased MDA concentrations in serum, liver and egg yolk by 39.3, 40.5 and 51.5%, respectively, in a dose-response manner. As supplemental C. arvense extract increased to 200mg/kg, the activity of hepatic SOD, CAT and GSH-Px increased by 14.5, 17.4 and 35.5%, respectively.5. Addition of C. arvense extract up to 200mg to per kg diet enhanced antioxidant status in laying quail and their eggs, without affecting performance and other egg quality parameters.6. Future studies are needed to elucidate the mechanism behind the antioxidant effects of C. arvense extract.
Keywords: Lipid-Peroxidation; Vitamin-E; Potential Mycoherbicide; Oxidative Stability; Phenolic-Compounds; Supplementation; Performance; Plants; Meat; Nonenolides